Bridging the digital divide: challenges and best practices in digitalizing rural schools - Amanda Joyce Honorious; Rosy Talin (Faculty of Education and Sports Studies, Universiti Malaysia Sabah, 2024)
Digitalization in education presents unique challenges, particularly in rural school settings. This qualitative study explores the digital transformation journey of three rural primary schools in Tuaran district, Sabah. The research focuses on the challenges faced by rural primary schools in adopting digital practices and identifies best practices to overcome these challenges. The research employs a qualitative approach. Interviews was conducted with the school headteacher and teachers involved in digitalization efforts. Findings reveal a range of challenges, including limited infrastructure, lack of technical expertise, resistance to change and struggle to integrate new digital tools into established teaching practices and administrative works. However, the study also identifies several best practices that have been successful in enhancing digitalization in rural schools, such as mentoring programs, professional learning community, change management and the gradual introduction of digital platforms to ease the transition. These practices have been successful in enhancing the school's data management and educational delivery, ensuring that pupils in rural areas are not left behind in the digital age. These findings have implications for policies and practices in rural education, highlighting the importance of tailored strategies to support digitalization efforts in rural schools.